(3GdGOGQI HGdPcGAGJ (B:s (3efgL GdJejR GdGSJQGJjLj h GdGLJeGYj ddefXeGJ (B/s - (3GdYRGhj, HTQi gGTes; (3GHQGgje, GHQGgje Ndjd s; (3UGdM, GMeO Ydj s ((3YeGf(B: s (3OGQ hGFd(B, s, 2009)
(3GdefXeGJ h GdGOGQI hGdPcGA eY GdJWQb Gdi CfhGY GdPcGA GdGSJQGJjLj hGdTYhQj h GdJfGaSj PGJ GdGQJHGW GdeHGTQ hGdUejej HYed GdefXeGJs
(3eQGLY(B: (3dcd aUd eQLYs
Keywords: (3EOGQI GdGYeGds; (3GdPcGAs; (3GdefXeGJs